Intimate Partner Violence and HIV Risk Behaviors Among Socially Disadvantaged Chilean Women - Miner, Sarah (2011)
The objective of this study was to determine if a relationship exists between intimate partner violence (IPV) and HIV risk among socioeconomically disadvantaged Chilean women. A correlational analysis with data from the NIH-funded project, “Testing an HIV/AIDS Prevention Intervention for Chilean Women,” was conducted. Two hundred and sixtyone women were included in this analysis (n = 261). Those women who had experienced any type of IPV in the past 3 months had significantly higher risk for HIV than those who had not (t = −2.016, p < .05). Also a linear trend was found among those women who had experienced more than one type of IPV in the past 3 months and HIV risk.